MOBILE TECHNOLOGY FOR PROMOTION OF TOURISM IN KASHMIR A STUDY OF SRINAGAR DISTRICT - Ahmad Dar, Showkat; Ahmad Lone, Naseer (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
Known as 'Heaven on Earth,' Srinagar lies on the Jhelum River in the Indian state of Jammu & Kashmir. Static houseboats and gondola-style rowboats, known locally as Shikaras, are a major tourist attraction in Srinagar. Srinagar, with its serene Dal and Nigeen Lakes, is a popular honeymoon and family vacation spot. In Srinagar, the city's summer capital, there's no shortage of hotels & resorts because it's one of Kashmir's most popular destinations. Srinagar welcomes visitors via a variety of mobile technologies and ensures that it has lodging that can accommodate their various requirements. The tourism industry in Jammu & Kashmir is being transformed by mobile technology. To efficiently market tourist destinations and services, mobile technology has become a crucial driver for the tourism business. With the help of mobile technology and the internet, a number of countries have grown their tourism sectors. However, the usage of mobile technology to promote the tourist attractions in Kashmir is still minimal and has to be improved upon. When ICT (information and communication technology) entered the picture, the world of tourism underwent a paradigm shift. The impact of technology on consumer travel and experiences is undeniable. Mobile technology is one of the many ICT tools that have influenced tourism destinations, visitors, communities, and other stakeholders for the betterment of the tourism sector as a whole. This article explores the ways in which mobile technologies have altered the tourism industry as well as the ways in which mobile technology innovation is driving this on-going development